Visual Haptic Approach Complements LearningProcess of Jawi Handwriting Skills - Maizan, Mat Amin; Halimah Badioze, Zaman; Azlina, Ahmad (2013)
Jawi handwriting skills are essential for Muslim pupils in the Malaysian education system. These skills are needed for them to properly learn the Islamic Education subject, apart from learning the language of the Holy Quran.The conventional methods of teaching Jawi handwriting skills are deficient in emphasizing the important aspects such as writing in correct sequences. It also lacks assestments during the process of writing. Therefore, it needs a new approach to enhance the learning process and the assessment of the Jawi handwriting skills. With its unique characteristics, the visual haptic approach could complement the learning process of Jawi handwriting skills. It is a promising aid in teaching and learning process of Jawi handwriting skills in primary schools and it can be implemented for other languages or other scripts handwriting skills as well.